Answer:
D. [tex](1,3)[/tex]
Step-by-step explanation:
Given
[tex]A = (-1,1)[/tex]
[tex]B = (3,0)[/tex]
[tex]C =(1,-4)[/tex]
[tex]A' = (0,4)[/tex]
[tex]B'=(4,3)\\[/tex]
[tex]C = (2,-1)[/tex]
Required
The translation vector
Represent the translation vector with [tex](x,y)[/tex]
Taking points A and A' as points of reference, we have:
[tex]A + (x,y) \to A'[/tex] ---- The translation
This gives:
[tex](-1,1) + (x,y) \to (0,4)[/tex]
Collect like terms
[tex](x,y) \to (0,4) -(-1,1)[/tex]
Rewrite as:
[tex](x,y) \to (0 - -1,4-1)[/tex]
[tex](x,y) \to (1,3)[/tex]
Hence, the translation vector is [tex](1,3)[/tex]